2011
DOI: 10.1111/j.1742-4658.2011.08262.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of antibacterial mechanism of l‐amino acid oxidase derived from Trichoderma harzianum ETS 323

Abstract: Although L-amino oxidase (LAAO; EC 1.4.3.2) has been reported to be a potent antibacterial agent, the mechanism responsible for its antibacterial activity has not been identified. The present study aimed to identify the mechanism responsible for the antibacterial activity of Th-LAAO, an LAAO recently isolated from the extracellular proteins of Trichoderma harzianum ETS 323, at the same time as elucidating the nature of this enzyme. The results obtained indicate that the enzyme activity and structure of Th-LAAO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Escapin, the defensive purple ink secretion component of the sea hare Aplysia californica, inhibited the growth of Gram-positive (B. subtilis with a MIC of 2.5 μg/mL) and Gram-negative bacteria (E. coli with a MIC of 0.62 μg/mL and S. typhimurium with a MIC of 0.62 μg/mL), as well as marine bacteria (Vibrio harveyi with a MIC of 0.25 μg/mL), pathogenic bacteria (S. aureus with a MIC of 0.31 μg/mL, S. pyogenes with MIC of 0.62 μg/mL, and P. aeruginosa with MIC of 0.31 μg/mL), yeast, and fungi . Moreover, Th-LAAO, the extracellular protein of soil bacterium Trichoderma harzianum induced damage to cells, lipid peroxidation, and DNA strand breakage in E. coli and S. aureus cells (Yang et al 2011). An LAAO from the marine bacterium Pseudoalteromonas luteoviolacea showed antibacterial activity against E. coli (Gómez et al 2008).…”
Section: Selective Antibacterial Actions Of Laaosmentioning
confidence: 98%
See 1 more Smart Citation
“…Escapin, the defensive purple ink secretion component of the sea hare Aplysia californica, inhibited the growth of Gram-positive (B. subtilis with a MIC of 2.5 μg/mL) and Gram-negative bacteria (E. coli with a MIC of 0.62 μg/mL and S. typhimurium with a MIC of 0.62 μg/mL), as well as marine bacteria (Vibrio harveyi with a MIC of 0.25 μg/mL), pathogenic bacteria (S. aureus with a MIC of 0.31 μg/mL, S. pyogenes with MIC of 0.62 μg/mL, and P. aeruginosa with MIC of 0.31 μg/mL), yeast, and fungi . Moreover, Th-LAAO, the extracellular protein of soil bacterium Trichoderma harzianum induced damage to cells, lipid peroxidation, and DNA strand breakage in E. coli and S. aureus cells (Yang et al 2011). An LAAO from the marine bacterium Pseudoalteromonas luteoviolacea showed antibacterial activity against E. coli (Gómez et al 2008).…”
Section: Selective Antibacterial Actions Of Laaosmentioning
confidence: 98%
“…Furthermore, bacteria treated with several LAAOs changed the morphology of the target cell (Vargas et al 2013;Vargas Muñoz et al 2014;Wang et al 2011;Ehara et al 2002;Kitani et al 2008;Kasai et al 2015) and membrane permeability (Yang et al 2011). The LAAOs-treated bacteria damaged the cell surface and formed surface aggregates, and the cells had a deformed appearance.…”
Section: Platichthys-stellatus--------------505--tsiysnlldvstqtrdef--mentioning
confidence: 99%
“…Although the cytotoxicity mechanisms of SV-LAAOs have not been fully clarified, it is known that lipids present in cell membranes can be damaged by reactive oxygen species (ROS) [28,29]. Considering that membranes of tumor cells present higher concentrations of lipids than normal cells, it is speculated that the hydrogen peroxide produced by LAAOs exerts direct action on the membrane of tumor cells, with lower toxicity on normal cells [30]. …”
Section: Reviewmentioning
confidence: 99%
“…Many studies of its biosynthesis have been reported (20)(21)(22)(23); however, there have been only a few reports on its antibacterial activity (27), and its mechanism of action remains unknown. Some L-amino acid oxidases, which catalyze oxidation reactions in which H 2 O 2 is among the products, have been reported to show antibacterial activity (25,26). H 2 O 2 formation is considered to be the cause of this activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some L-amino acid oxidases that produce H 2 O 2 during oxidation reactions are known to show antibacterial activity (25,26). Although ACT has antibiotic activity (27), its mechanism of action in bacteria remains unknown.…”
Section: Identification Of Reaction Products and Stoichiometry Of Oximentioning
confidence: 99%